KAJIAN TINGKAT DEGRADASI LAHAN DAN KEMAMPUAN LAHAN PADA USAHATANI LAHAN KERING BERBASIS TEMBAKAU DI SUB-DAS PROGO HULU - Jaka Suyana (Faculty of Agriculture, Universitas Sebelas Maret, 2009)
Title : The study of land capability and land degradation level on tobacco-based upland farming at Progo Hulu Sub-watershed. The recent and also the future problems for Indonesian concerning with agricultural environment resources are land degradation and water resources restrictiveness. Agricultural technique without awareness to concerning to soil and water conservation principles on steep and high rainfall area had caused severe erosion and land degradation at upland area of Progo Hulu sub-watershed. Land Degradation that promoted by erosion at Progo Hulu sub-watershed contributed negative effects at on-site and out-site area. The results showed that: (1) The degradation levels on upland farming area of Progo Hulu sub-watershed (7.398,54 ha) are classified as: low (708.71 ha or 9.58%), moderate (5,119.15 ha or 69.19%) and high (1,570.68 ha or 21.23%); (2) The land capability classes were dominated by Class IV (3,624.93 ha or 49.00%), followed with Class VI (2,488.82 ha or 33.64%), Class III (697.99 ha or 9.43%), Class V (450.73 ha or 6.09%), and Class VII (136.06 ha or 1.84%). Keywords: land capability, land degradation, Progo Hulu Sub-watershed